Surgical management of congestive heart failure - Fang, James C. (Contemporary cardiology)
Surgical therapy for advanced heart failure has been traditionally limited to cardiac transplantation. Historically, other surgical interventions on the failing heart have been limited by significant perio-operative morbidity and mortality and a lack of evidence that such surgical interventions improved long-term outcomes. Moreover, cardiac transplantation is limited by the lack of donor organs, and advances in medical management have primarily only slowed disease progression. However, recent improvements in surgical techniques and rapid advances in device technology can now produce predictable benefits and acceptable mortality for these very ill patients. For these reasons, surgery and device therapy is likely to play an increasingly dominant role in the management of advanced heart failure during the next decade. In Surgical Management of Congestive Heart Failure, James C. Fang, MD, and Gregory S. Couper, MD, have assembled a panel of prominent surgeons and cardiologists to review the latest clinical, scientific, and investigational surgical and mechanical approaches to heart failure in hopes of improving the lives of this challenging group of patients. Topics range from such traditional strategies as high-risk surgical revascularization in advanced coronary artery disease to more novel approaches, such as ventricular reconstruction and mechanical assist devices. Many chapters are contributed by the original pioneers of specific surgical techniques, which provides invaluable perspective from personal experience. Authoritative and multidisciplinary, Surgical Management of Congestive Heart Failure offers a state-of-the-art review of the significant surgical and mechanical options available for the optimal treatment of end-stage heart failure patients. Recent advances in cardiac allotransplantation - Surgical revascularization in the management of heart failure and ischemic left ventricular dysfunction - Aortic valve surgery with severe left ventricular dysfunction - Mitral valve surgery with severe left ventricular dysfunction - Tricuspid valve surgery in right heart failure - Pacing in heart failure - Left ventricular assist devices - Left ventricular volume reduction surgery for idiopathic dilated cardiomyopathy - Surgical management of hypertrophic cardiomyopathy - Dynamic cardiomyoplasty and new prosthetic lv girdling devices - Xenotransplantation - Left ventricular reconstruction for ischemic heart failure - The total artificial heart in the surgical management of congestive heart failure.